1992
DOI: 10.1007/bf00338053
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between odontoblasts and pulp capillaries in the process of enamel- and cementum-related dentin formation in rat incisors

Abstract: The relationship between odontoblasts and pulp capillaries in the process of dentinogenesis was studied in rat lower incisors, both on the labial and lingual sides, using light and transmission electron microscopy. The odontoblasts showed remarkable differences from the apical to the incisal end. Near the apical end of the tooth, "immature odontoblasts", which were thought to be involved in the formation of the mantle dentin, were arranged in a single layer, and continuous capillaries were located just beneath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
36
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 26 publications
1
36
0
Order By: Relevance
“…Matrix-producing cells increasing the expression of their nestin and Dsp are referred to as odontoblasts, and these cells are further divided into subgroups. In our previous study using continuously growing rat incisor teeth, we have divided these cells into three types: immature, mature, and post-odontoblasts, according to their morphology, the rate of dentin deposition, and their nutritional supply (the location and ultrastructure of the odontoblastic capillaries) (39). The cells beginning to produce predentin are characterized by immature features including minute projections on their distal ends and are engaged in the production of mantle dentin where no capillaries are present in the odontoblast layer.…”
Section: Classification Of Odontoblast-lineage Cells (Table 3)mentioning
confidence: 99%
See 3 more Smart Citations
“…Matrix-producing cells increasing the expression of their nestin and Dsp are referred to as odontoblasts, and these cells are further divided into subgroups. In our previous study using continuously growing rat incisor teeth, we have divided these cells into three types: immature, mature, and post-odontoblasts, according to their morphology, the rate of dentin deposition, and their nutritional supply (the location and ultrastructure of the odontoblastic capillaries) (39). The cells beginning to produce predentin are characterized by immature features including minute projections on their distal ends and are engaged in the production of mantle dentin where no capillaries are present in the odontoblast layer.…”
Section: Classification Of Odontoblast-lineage Cells (Table 3)mentioning
confidence: 99%
“…A lower level of expression for these proteins has also been found in non-mineralized tissues such as the brain, kidney, pancreas, and salivary gland (53). Among them, the intermediate filament nestin is considered as a marker for differentiated odontoblasts in developing teeth and newly-differentiated odontoblast-like cells apimmature and mature odontoblasts (39). Rodent incisors are continuously growing teeth, for which all stages of odontogenesis-including amelogenesis and dentinogenesis-can be surveyed if the sections of the tooth are prepared from the apical end to the incisal edge (39,48).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The measuring points were selected based on the previous reports (Weinreb and Weinreb, 1986;Ohshima and Yoshida, 1992;Tabata et al, 1993;Yoshida and Ohshima, 1996), and the reported values comparable to those of the control animals of the present study.…”
Section: Measurements Of Blood Camentioning
confidence: 98%